Corporate Social Responsibility and Customer Satisfaction in Malaysian Hotels: Mediator of Brand Image and Corporate Reputation - Li, Niu; Abdullah, Zulhamri Bin; Mahamed, Mastura Binti; Huiying, Long; Meng, Qi (Journal of Ecohumanism, 2025)
Grounded in stakeholder theory, this research explores how various aspects of corporate social responsibility (CSR)—namely economic, ethical, legal, and philanthropic—relate to customer satisfaction within Malaysia's hotel sector.Specifically, it examines the mediating roles of brand image and corporate reputation in shaping customer perceptions and responses to CSR initiatives. A quantitative research approach was employed, utilizing data from 438 customers of five-star hotels in Kuala Lumpur. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data and test the hypothesized relationships.The findings reveal that ethical and philanthropic CSR practices significantly enhance brand image, while economic and philanthropic CSR initiatives positively influence corporate reputation. Furthermore, legal and ethical CSR dimensions contribute to corporate reputation, emphasizing the importance of socially responsible business operations. The study confirms that CSR, across its various dimensions, has a direct and positive impact on customer satisfaction within the Malaysian hotel industry. Importantly, Brand image and corporate reputation act as key mediators in the link between CSR initiatives—particularly the economic and philanthropic dimensions—and customer satisfaction.highlighting their role in strengthening consumer trust and loyalty.These results provide valuable managerial insights, suggesting that hotel operators should integrate CSR into their strategic branding and corporate identity efforts.